Pendampingan Melek Jurnalistik di MA Ma’arif 7 Sunan Drajat - Sunaji, Sunaji (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The aim of Community Assistance activities is to improve journalistic understanding and skills for students at Madrasah Aliyah Ma'arif 7 Sunan Drajat. This mentoring method is direct learning, training, workshops and intensive guidance. The results of this journalistic mentoring activity were very effective in increasing students' understanding of the basic principles of journalism. Improve your ability to write news and create written works in print and electronic media